Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Minat Belajar Ips Siswa Kelas Iv SD Inpres 2 Kamonji - Alfionita; Nuraini, Nuraini; Firmansyah, Arif; Muchdar, Muchdar (JURNAL DIKDAS, 2022)
This research aims to determine the influence of the use of the Teams Games Tournament (TGT) type cooperative model on the science and science learning outcomes of grade IV students at SD Inpres Bumi Sago. This research is experimental research conducted in one experimental class. The research design used in this research is Pre-Experimental Design in the form of One Group Pretest Posttest. The population in this study was 24 grade IV students at SD Inpres Bumi Sago for the 2024 academic year. The sample in this study was all class IV which was the experimental class. The instrument used is a test instrument, namely multiple choice questions whose validity and reliability have been tested. Data analysis used prerequisite tests, namely normality and linearity tests and hypothesis testing using paired sample t-test which was analyzed using SPSS 22 for windows. Based on the results of this research, it shows a significance value of 0.000 < 0.05, so accepting the Ha hypothesis and rejecting the Ho hypothesis, this means that there is an influence of the use of the TGT type cooperative model on the learning outcomes of fourth grade students at SD Inpres Bumi Sago. So it can be concluded that there is an influence of the use of the Teams Games Tournament (TGT) type cooperative model on the science and science learning outcomes of Inpres Bumi Sago Elementary School students